Are Certain Dividend Increases Predictable? The Effect of Repeated Dividend Increases on Market Returns. Issue 4 (December 2014) - Michayluk, David; Neuhauser, Karyn; Walker, Scott
<x xml:space="preserve">Abstract</x> The authors report the findings of their study of over 400 stocks of public companies that announced at least 20 consecutive increases in their dividends during the period 1999 and 2009. With the assumption that the stock market learns to anticipate future dividend increases from current patterns, the study was designed to answer the question: How many increases does it take for the market to anticipate, and "price in, " the pattern of dividend increases? The authors report finding that abnormal returns around the first and second announcements of dividend increases are significant and positive, but are much less significant for the third and further increases. They also find that the size of the dividend increases tends to fall with more increases, and that the largest percentage dividend changes occur early in the sequence.